We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
102
1
avatar

The explicit rule for a sequence is given.

 

an = 2/5(5)^n - 1

 

Enter the recursive rule for the geometric sequence.

 

a1=                  an=

 Feb 13, 2019
 #1
avatar+101871 
+1

I'm assuming that this is

 

an = (2/5)(5)^(n - 1)

 

Recursive rule

 

an  =  an-1 *  (5),   where a1 =  (2/5)

 

cool cool cool

 Feb 13, 2019

4 Online Users